Goal-Oriented Ethics: Framing the Goal-Setting Concretely - Illathuparampil, Mathew (Religions, 2017)
Joseph Selling, professor emeritus from KU Leuven, Belgium, recently made a significant contribution towards ethical methodology. It is in fact a continuation of the in-house conversations that have been in vogue about methods in moral reasoning since Vatican II in the discipline called theological ethics. What is specific about Selling's attempt is that he re-orients or reframes the evaluation of the moral event to consider human intentionality or motivation before considering human behavior or human acts. He convincingly establishes his method by a meticulous reading of Thomas Aquinas. This paper is a response to the goal-oriented ethics that he has posited. As illustrated below, this paper evaluates the goal-oriented approach as solid and sufficient. While fully endorsing this approach, this paper argues that the process of ethical goal-setting is to be framed concretely. In a concrete historical context, so that a goal-oriented approach fully serves its purpose, this paper proposes that it is to be reinforced by four supportive pillars, which are in fact assumed by Selling in his work. They are openness to human sciences, conversation among various narratives, positing a theological frame for ethical reasoning, and recourse to non-discursive reasoning.